Peran Koperasi Gotong Royong Dalam Meningkatkan Perekonomian Anggota Di Kelurahan Binjai Serbangan - Ripho Delzy Perkasa; Najwa Zahra; Rahma Mahrani Sam Harahap; Giska Nayla Maqah (CV. Ulil Albab Corp, 2024)
The aim of this research is to determine the role of Mutual Cooperation Savings and Loans Cooperatives in the development of Micro, Small and Medium Enterprises (MSMEs) in Binjai Serbangan Village, as well as as a place to store money for members and also improve the economy of the community in Binjai Serbangan Village. The research used is a qualitative method. The techniques used are observation, interviews and documentation. The number of informants in this research was 3 people, including the chairman of the Mutual Cooperation Savings and Loans Cooperative and 2 members of the Mutual Cooperation Savings and Loans Cooperative. The results of this research are: 1) Development of Micro, Small and Medium Enterprises (MSMEs) in Binjai Serbangan Subdistrict, namely by lending business capital to members. 2) Become a place to store money for its members like other financial institutions. 3) As well as improving the community's economy, especially members of the cooperative. Based on research activities on Savings and Loans Cooperatives that have been carried out, there are several important roles of cooperatives, namely they have an important role in supporting the business growth of their members, fostering an entrepreneurial spirit, and creating new business opportunities. And the success of a cooperative is measured by its ability to develop and dominate the market.